(untitled) (Nusantara of Engineering (NOE), 2026)
Cultivating students’ interest in learning is the key to creating an effective and meaningful learning process, especially in Informatics subjects, which are often considered boring when delivered theoretically. This study aims to develop interactive learning media in the form of educational games based on Wordwall to foster junior high school students’ interest in learning Microsoft PowerPoint material. The method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Validation results from material and media experts indicate that the developed media is relevant and feasible to use. The application of Wordwall in learning has been proven to foster students’ interest in learning, as shown by the questionnaire results, which obtained a score of 73%, falling into the "High" category. Therefore, the use of Wordwall is effective as an interactive learning medium that can increase students’ engagement and enthusiasm for theoretical material in Informatics lessons.